Pelayanan Website Aku Online-NG dalam Peningkatan Pelayanan Administrasi Kependudukan di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Buleleng - Ananda Wahyu Muditha; I Dewa Ayu Putri Wirantari; Ni Putu Anik Prabawati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The aim of this research is to find out how to improve population administration services in Buleleng Regency through the use of the Aku Online-NG website which will be implemented in 2022, where in its implementation there are still several obstacles. Using qualitative descriptive research. Data sources are primary data and secondary data. The data collection techniques used were interviews, documentation and observation. Data analysis techniques are data reduction, data presentation and drawing conclusions. The problem in this research is in the form of public complaints about the variety of features and performance of the Aku Online-NG website. The theory used is e-government with a service quality measurement method called egovqual. Guided by the Presidential Regulation of the Republic of Indonesia Number 95 of 2018 concerning Electronic-Based Government Systems. Based on the research results, it can be concluded that in the ease of use dimension, the department has provided very good convenience and the community has also made things easier with this innovation. The reliability dimension shows good results which can be seen from the opinions of the public who feel this website is very reliable. The trust dimension has been implemented well, where the security of public data is guaranteed with the JSON Web Token (JWT) security system. The content & appearance of information dimensions have not been running optimally due to the lack of service features related to the movement of families from outside the district to within the district. In the dimension of functionality of the interaction environment, it is not yet fully maximized because some people still feel that filling out forms is rather difficult through online-based services. Then the last dimension, namely citizen support, has gone quite well, but there are still shortcomings, namely the lack of outreach carried out by the department to the community. It is hoped that the results of this research can be utilized as needed by relevant agencies and for further research.